Using NVivo to Identify Cultural, Social, and Contextual Factors Influencing Leadership Practices in Islamic-based Schools: A Qualitative Research - Sulisworo, Dwi; A’yun, Ummu Qurrata; Maryani, Ika (Universitas Ahmad Dahlan, 2025)
This research aims to explore the cultural, social, and contextual factors that influence the practices of transformational leaders in Islamic-based schools, focusing on how these factors shape leadership styles and decision-making processes. Utilizing qualitative methods and NVivo software for data analysis, the study examines the roles of cultural values, social awareness, and community involvement in shaping the leadership practices of school principals. NVivo was employed to analyze and visualize key themes through tools such as word clouds, project map diagrams, and hierarchy charts, which helped identify and organize the most frequently mentioned concepts and relationships within the data. The findings highlight the significant impact of Islamic teachings, such as discipline, respect, cooperation, and transparency, in guiding leadership behaviors and decision-making. Culturally, leadership is deeply rooted in Islamic principles, fostering a supportive and inclusive school environment. Socially, leadership practices emphasize empathy, solidarity, and mutual aid, influencing leaders’ decisions in favor of the collective good. Contextually, routine religious practices and active community involvement contribute to the holistic development of students and staff, reinforcing the principles of collaboration and shared responsibility. Overall, this study underscores the importance of cultural, social, and contextual factors in shaping transformational leadership in Islamic-based schools, illustrating how these elements guide both leadership styles and decision-making processes toward achieving educational and spiritual goals.